Understanding the experience of psychopathology after intimate partner violence: the role of personality - Paulo A.S. Moreira; Márcia Pinto; C. Robert Cloninger; Daniela Rodrigues; Carlos Fernandes da Silva (PeerJ, 2019)
Objective(s) To fully understand the dynamics of Intimate Partner Violence (IPV) it is necessary to understand the role of personality. The current understanding of which personality characteristics are associated with IPV victimization is, however, far from comprehensive. Given this gap in the literature, our objective was to examine the associations between the dimensions of the psychobiological model of personality and psychopathological symptoms in women who had experienced IPV. Methods Using a case-control design, a group of women who had experienced IPV and who were living in shelters (n = 50) were compared to a group of control women who had not experienced IPV (n = 50). All women completed the Temperament and Character Inventory–Revised and the Brief Symptom Inventory. Results Victims of IPV showed significantly higher levels of Harm Avoidance and Self-Transcendence, and lower levels of Reward Dependence and Self-Directedness, than the non-IPV control group. Victims of IPV also reported elevated levels of psychopathological symptoms. Personality dimensions showed a broadly consistent pattern of associations across different psychopathological symptoms. A regression analysis indicated that Novelty Seeking was negatively associated with psychopathological symptoms in victims of IPV, but not significantly associated in non-victims. Conclusions The study highlights the important role of Harm Avoidance and Self-Directedness for understanding psychopathological symptoms. Novelty Seeking appears to play an important role in the expression of individuals’ experiences of IPV. These results have important implications for research and practice, particularly the development and implementation of interventions.